2020
DOI: 10.1111/cdev.13474
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Established Joint Attention in Hearing‐Hearing and Hearing‐Deaf Mother‐Child Dyads: Associations With Social Competence, Settings, and Tasks

Abstract: The authors examined relations among observed joint attention, maternal report of child’s social competence, setting (home vs. laboratory), task (unstructured vs. semi‐structured), and dyad type [hearing mother–hearing child (n = 55, Mage = 25.8 months) vs. hearing mother–deaf child (n = 27, Mage = 26.9 months)]. Hearing child dyads scored higher on joint attention during unstructured tasks, especially in their home environment. Hearing child dyads displayed similar joint attention to deaf toddler dyads when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Another factor that could be important in terms of deaf children with CIs is the quality and quantity of joint attention between the child and caregiver [79]. For example, MacGowan et al [80] found that joint attention scores between hearing mothers and deaf children aged from 17 to 41 months (including deaf children with CIs) were positively related to the child's social competence as reported by the mother. Interestingly, this relationship was not observed in the hearing dyads.…”
Section: Tom Development In Deaf Children With Cismentioning
confidence: 99%
“…Another factor that could be important in terms of deaf children with CIs is the quality and quantity of joint attention between the child and caregiver [79]. For example, MacGowan et al [80] found that joint attention scores between hearing mothers and deaf children aged from 17 to 41 months (including deaf children with CIs) were positively related to the child's social competence as reported by the mother. Interestingly, this relationship was not observed in the hearing dyads.…”
Section: Tom Development In Deaf Children With Cismentioning
confidence: 99%